Arabidopsis thaliana RNase H2 Deficiency Counteracts the Needs for the WEE1 Checkpoint Kinase but Triggers Genome Instability . Issue 9 (12th September 2014) - Kalhorzadeh, Pooneh; Hu, Zhubing; Cools, Toon; Amiard, Simon; Willing, Eva-Maria; De Winne, Nancy; Gevaert, Kris; De Jaeger, Geert; Schneeberger, Korbinian; White, Charles I.; De Veylder, Lieven
Abstract : Absence of the RNAse H2 complex, mediating the excision of ribonucleotides from DNA, was found to overcome the growth inhibitory phenotype of plants lacking a functional replication checkpoint because of tolerating the substitution of deoxynucleotides with ribonucleotides. This substitution, however, results in replication errors, demonstrating the need of RNase H2 activity for genome stability. Abstract: The WEE1 kinase is an essential cell cycle checkpoint regulator in Arabidopsis thaliana plants experiencing replication defects. Whereas under non-stress conditions WEE1 -deficient plants develop normally, they fail to adapt to replication inhibitory conditions, resulting in the accumulation of DNA damage and loss of cell division competence. We identified mutant alleles of the genes encoding subunits of the ribonuclease H2 (RNase H2) complex, known for its role in removing ribonucleotides from DNA-RNA duplexes, as suppressor mutants of WEE1 knockout plants. RNase H2 deficiency triggered an increase in homologous recombination (HR ), correlated with the accumulation of γ-H2AX foci. However, as HR negatively impacts the growth of WEE1 -deficient plants under replication stress, it cannot account for the rescue of the replication defects of the WEE1 knockout plants. Rather, the observed increase in ribonucleotide incorporation in DNA indicates that the substitution of deoxynucleotide with ribonucleotide abolishes the need for WEE1 under replication stress. Strikingly, increased ribonucleotide incorporation in DNA correlated with the occurrence of small base pair deletions, identifying the RNase H2 complex as an important suppressor of genome instability.